(untitled) (Research, Society and Development, 2024)
This study is an integrative review (IR), of the literature, that aims to describe which cognitive aspects are seen and exercised in auditory training programs for elderly hearing aid users. The research question was “What cognitive skills are practiced in informal auditory training programs for elderly hearing aid users?”. The inclusion criteria were articles published in the last 10 years (2014-2024), in Portuguese, English, or Spanish, in the population aged 60 and over, which fit the proposed theme. The exclusion criteria were duplicate articles in the databases, articles that even, after full reading, didn’t answer the research question, and studies that referred to cochlear implants. The collection resulted in 106 articles (BVS=32; 30.2%/ PubMed= 28; 26.4%/ Cochrane= 46; 43.4%), 22 duplicates between the databases and 69 studies were excluded after the first reading of the title and abstract. This resulted in 15 articles to be read in full. After a detailed reading of these studies, 11 manuscripts were excluded, leaving four articles. This integrative review has provided an overview that can guide researchers and clinicians in two ways: to anticipate the planning and structuring of future research and interventions involving cognitive training in elderly hearing aid users.